Survey Of Futsal Players' Extra-Curicular Student Passing Ability Level State Primary School 146 Bengkulu Utara - Aji, Afwan Fiki; Sumantri, Ajis; Sembiring, Lina Tri Astuty Beru (Educative Sportive, 2024)
The aim of this research is the level of inner leg passing ability of futsal players among futsal extracurricular students at SDN 146 North Bengkulu Regency. This type of research is survey research with a quantitative descriptive approach. The subjects of this research were 20 Futsal Extracurricular Students at SDN 146 North Bengkulu Regency. Data collection techniques using dribbling tests. Data analysis using quantitative descriptive analysis with percentages. The research results were 1 person with a percentage (5.0%) in the very good category, 7 people with a percentage (35.0%) in the good category, 2 people with a percentage (10.0%) in the medium category, 9 people with a percentage (45.0%) in the poor category and 1 person percentage (5.0%) in the very poor category. The conclusion obtained is that the level of inner leg passing ability of futsal players of futsal extracurricular students at SDN 146 North Bengkulu Regency is in the poor category.